Survey data on the international public’s perceptions of child maltreatment and related subjectsOpen Sciene Framework - Tomoya Mukai; Tomohiro Ioku; Aki Akanmie; Yoshiko Habuchi; Yuma Matsuki; Shuma Iwatani; Akiko Tanaka; Yuki Yuyama; Eiichiro Watamura (Data in Brief, 2025)
This study explores international differences in public perceptions of child maltreatment and the institutions addressing it based on a dataset collected from 2722 respondents across nine developed countries: Denmark, Finland, France, Germany, Japan, Sweden, Taiwan, the UK, and the US. By investigating trust, perceived competence, and warmth toward public institutions, as well as perceived causes of child maltreatment, the study offers a comprehensive cross-cultural understanding of public attitudes. The data were collected through a standardized survey method with samples stratified by age, gender, and residence according to national censuses, ensuring representativeness. The findings reveal significant variations in how institutions and their staff are perceived in terms of trust, competence, and societal roles across countries. This suggests cultural and systemic differences influence public acceptance of institutional interventions in child maltreatment cases. Furthermore, the dataset enables the exploration of critical factors, such as the perceived causes of maltreatment and the impact of media exposure, which shape public attitudes and cooperation with formal institutions. This dataset holds practical and theoretical value by providing policymakers and researchers with a foundation for analyzing institutional effectiveness and public engagement strategies in addressing child maltreatment. The open accessibility of the dataset ensures its utility for cross-disciplinary research, fostering international collaboration and policy development. This study contributes to the growing discourse on how societal perceptions influence child protection measures and highlights the need for culturally sensitive approaches in combating child maltreatment.